The Development of a Management System for The National Sports Development Fund in Thailand - Jaruwan Ployduangrat (My University, 2022)
The purposes of the current study were to develop a management system for the national sports development fund in Thailand and 2) to evaluate the developed fund management system. The participants were 15 experts in system development. They were selected by the purposive sampling method. The participants had more than 10 years of programming and system development. The instrument included a management system for the national sports development fund in Thailand and a system evaluation form. The data were analyzed using percentages, mean scores, and standard deviation. The results of the study indicate that the developed management system for national sports development in Thailand has 3 main functions including e-documents, e-tracking, and e-payment. It was also found that the system shows good qualities in terms of functional requirements, functions, usability, and security. The results of the study could be implicated in the design of a technology-based research management system in terms of technology and components employed in the design of the system.
Keywords: Payment system; Security system; Big Data and Business Intelligence